Legal Protection for Communities Victims of Environmental Damage due to illegal mining in Lampur Village, Central Bangka - Situmorang, Greace Naomi; Br, Julia Serpita; lonika, Tesa (CV. Publikasi Indonesia, 2024)
Mining is a promising natural resource to support the economy of a country and also the local government. Mining activities that are made into livelihoods have shown income for the community, especially dasa lampur, Central Bangka. So that a lot of people are involved in mining. Moreover, illegal mining. But natural resources such as tin cannot be renewed. The purpose of this research is to determine whether there is legal protection for victims of environmental damage due to illegal mining in Lampur village, Central Bangka. The method used in this research is the normative-empirical method, using a legislative approach, and interviewing the local community. The results of the research, in general, people in Lampur village carry out mining activities because of economic interests so that this research provides information to the community how important it is to protect the environment and their own safety.